Integrated Rural Energy Planning Programme in the Seventh Plan Training Manual - Planning Commission (Planning Commission, 1987)
The Integrated Rural Energy Planning Programme (IREP) is a comprehensive initiative aimed at improving energy access, sustainability, and rural development in India. Initiated during the Sixth Plan and expanded in the Seventh Plan, IREP emphasizes the optimal mix of conventional and renewable energy sources tailored to local community needs. The program combines central and state-level components, supported by training initiatives and institutional frameworks to enhance planning, implementation, and monitoring. Key strategies include demand assessment, technology evaluation, cost-benefit analysis, and the promotion of biogas, solar, and wind energy. The program also stresses community participation, capacity building, and integration of energy planning into broader rural development frameworks. IREP aims to reduce reliance on non-commercial energy sources, increase renewable energy use, and foster socio-economic improvements in rural areas, while ensuring environmental sustainability.
Rural Energy Division Planning Commission Government of India
Rural Energy Division Planning Commission Government of India
Keywords: Integrated Rural Energy Planning; Renewable Energy; Rural Development; Biogas; Solar Energy; Energy Sustainability; Energy Access; Capacity Building; Institutional Framework; Cost-Benefit Analysis